Iron dictates the growth, biofilm formation, and virulence of Pseudomonas aeruginosa in pulmonary infections - An, Chao; Chen, Ruan; Wu, Baijian; Chen, Shanjian; Zou, Shenghua; Lin, Yulan; Yang, Bin; Luo, Chenshuo (Frontiers in Microbiology, 2026)
BackgroundPseudomonas aeruginosa is the most prevalent pathogen responsible for persistent pulmonary infections. Iron concentrations in the human lung are known to vary considerably between health and disease states. We hypothesized that increased iron availability is a key driver of persistent infection establishment and sought to define the impact of iron on P. aeruginosa in the context of persistent lung infection.MethodsClinically isolated strains of P. aeruginosa from persistent lung infections and the reference strain PAO1 were collected. We examined bacterial growth rates, virulence determinants such as biofilm formation and pyocyanin production, and adhesion to lung epithelial cells under different iron conditions. Virulence was assessed using a Galleria mellonella model, and pathogenicity was evaluated in a mouse model.ResultsCompared to P. aeruginosa grown in iron-deficient medium, bacteria cultured in iron-rich medium exhibited significantly enhanced growth rates and biofilm formation, while virulence determinants were attenuated. The Galleria mellonella model also showed reduced virulence. Additionally, iron-rich conditions enhanced bacterial adhesion to lung epithelial cells. In the mouse model, weakened pathological damage and higher bacterial loads in the lungs were observed.ConclusionOur findings indicate that environmental iron facilitates the growth and biofilm formation of P. aeruginosa causing pulmonary infections, while attenuating its virulence. This iron-mediated adaptation may be associated with the persistence of P. aeruginosa pulmonary infections, and these findings merit further investigation.